Pengaruh Internet Banking dan Mobile Banking Terhadap Kinerja Bank Umum Konvensional di Indonesia - Mazia Ardyne Dyani Saputra; Halimah Husna Rofiqoh; Wendy Saputra (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Banking has a major role as an intermediary institution that aims to support national economic growth. The main function of banking in the economy is to collect public funds and distribute these funds for economic activities. Today, people are being introduced to internet banking and mobile banking, both of which are products produced by banking institutions. This product is a breakthrough for the challenges of the times where technology is rapidly increasing and information systems are circulating very quickly. Therefore, these products are the answer to the current challenges. However, the reality must be known and assessed whether these products contribute in this case to the performance of the banking sector. From these problems, researchers try to do research on these variables. What happens if internet banking and mobile banking are implemented in banking services. Is it a good influence or vice versa. This research was conducted on a sample of four large banks in Indonesia which researchers believe can represent the entire population studied. Testing this research using multiple linear regression test through Eviews software. The data for this study uses secondary data obtained through reliable sources with the type of time series data from June 2020 to November 2022. This research is regression from ROA data and internet and mobile banking data. The results of the research analysis show that there is a significant influence from internet banking and mobile banking on banking performance in Indonesia.